Cybersecurity Analysis of Information Technology Infrastructure in the Era of Cloud Computing - Siti Khodijah; Sitha, Nur Syifa’u; Syafawi, Raihan (Prosiding Seminar Nasional Ilmu Komputer, Sosial Sains, Teknik dan Multi-Disiplin Ilmu, 2025)
In the era of cloud computing, cybersecurity has become a critical concern for organizations relying on digital infrastructure. The rapid adoption of cloud-based systems offers scalability, flexibility, and efficiency, yet it simultaneously introduces complex security challenges such as data breaches, unauthorized access, and system vulnerabilities. This paper presents an analytical study of cybersecurity issues affecting information technology (IT) infrastructure in the cloud computing environment. The research explores potential threats, evaluates existing security frameworks, and discusses strategies for enhancing data protection and risk management. A mixed-method approach, combining literature review and case analysis, was employed to identify key factors influencing cloud security performance. The findings reveal that while cloud service providers implement robust security measures, human error, weak authentication mechanisms, and inadequate policy enforcement remain major risk factors. The study emphasizes the importance of adopting a multi-layered security model, integrating encryption, identity management, and continuous monitoring to ensure data integrity and confidentiality. In conclusion, maintaining cybersecurity in the cloud era requires a balance between technological innovation and organizational awareness. Strengthening cybersecurity resilience demands collaboration among stakeholders, continuous updates of security protocols, and the development of adaptive policies aligned with emerging threats.